2015
DOI: 10.1128/genomea.00706-15
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Tomato Mosaic Virus Isolated from Jasmine in the United States

Abstract: Tomato mosaic virus was reported from jasmine in Florida. We present the first complete genome sequence of a tomato mosaic virus isolate from this woody perennial plant in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…ToMV was first reported in 1909 in the USA and can infect a wide range of plant species, causing losses in many economically important crops [ 12 ]. ToMV is widely distributed in many countries and global regions, including China [ 10 , 16 , 22 , 23 , 24 , 25 ]. For the past several years, the presence of ToMV in tomato growing areas has been dominant and consistent in three provinces of China due to the stable nature of its viral particles, its long survival period in crop hosts, its easy mechanical and rapid transmission through field workers and agricultural instruments [ 26 ], and its resistance to elimination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ToMV was first reported in 1909 in the USA and can infect a wide range of plant species, causing losses in many economically important crops [ 12 ]. ToMV is widely distributed in many countries and global regions, including China [ 10 , 16 , 22 , 23 , 24 , 25 ]. For the past several years, the presence of ToMV in tomato growing areas has been dominant and consistent in three provinces of China due to the stable nature of its viral particles, its long survival period in crop hosts, its easy mechanical and rapid transmission through field workers and agricultural instruments [ 26 ], and its resistance to elimination.…”
Section: Discussionmentioning
confidence: 99%
“…ToMV was first reported in 1909 in the USA and can infect a wide range of plant species, causing losses in many economically important crops [12]. ToMV is widely distributed in many countries and global regions, including China [10,16,[22][23][24][25]. For the…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed that variences in hosts did not lead to a difference in similarity rates. Fillmer et al [35] deposited the rst whole genome sequence of a ToMV isolate from jasmine in the NCBI GenBank with the accession number KR537870. In phylogenetic analysis, they found 99% identity with the reference ToMV sequence.…”
Section: Duarte Et Al [46] Isolated Tomv From Hemerocallis Sp (Tobamo...mentioning
confidence: 99%